2001
DOI: 10.1093/mutage/16.6.499
|View full text |Cite
|
Sign up to set email alerts
|

Induction of micronuclei in mice exposed to static magnetic fields

Abstract: The aim of this experiment was to investigate whether static magnetic fields (SMFs) have cytogenetic effects in mouse bone marrow cells. The frequency of micronuclei was significantly increased by exposure of mice to 3.0 T for 48 and 72 h and 4.7 T for 24, 48 and 72 h. The increase in micronucleus frequency was dose dependent at all times. Micronucleus frequency at 4.7 T was higher than at 3.0 T. We consider that the increased numbers of micronuclei may be attributable to a stress reaction caused by SMFs or a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 18 publications
(15 reference statements)
2
20
0
2
Order By: Relevance
“…We also previously reported the suppression or enhancement of the genotoxic effects in microbial systems, cultured cells and animals, the suppression of food and water consumption and body weight in mice, and the enhancement of metallothionein content and lipid peroxidation in mice, with exposure to strong static EMFs (0.15-to 11.75-T) alone or co-exposure to static EMFs and chemicals (38)(39)(40)(41)(42)(43). Our previous studies suggested that the effects induced by strong static EMFs may be enhanced or suppressed by the stress reaction or cell cycle change.…”
Section: Discussionmentioning
confidence: 94%
“…We also previously reported the suppression or enhancement of the genotoxic effects in microbial systems, cultured cells and animals, the suppression of food and water consumption and body weight in mice, and the enhancement of metallothionein content and lipid peroxidation in mice, with exposure to strong static EMFs (0.15-to 11.75-T) alone or co-exposure to static EMFs and chemicals (38)(39)(40)(41)(42)(43). Our previous studies suggested that the effects induced by strong static EMFs may be enhanced or suppressed by the stress reaction or cell cycle change.…”
Section: Discussionmentioning
confidence: 94%
“…However, the International Agency for Research on Cancer (IARC) proposed that SMFs might affect embryonic development in amphibians (International Agency for Research on Cancer, 2002). SMFs have been reported to be toxic to rat embryos (Mevissen et al, 1994), and to cause significant time-and dose-dependent increases in the frequency of micronuclei in mice (Suzuki et al, 2001) and in the rates of germination and early growth in Cicer arietinum L. (Ananta and Shantha, 2008). Various studies have focused on the effects of SMFs on the nervous system, behavior, genotoxicity and cancer incidence.…”
Section: Introductionmentioning
confidence: 99%
“…However, some genotoxic effects of MRI scanning have been demonstrated under in vivo as well as in vitro conditions (Suzuki et al, 2001;Simi et al, 2008;Lee et al, 2011;Fiechter et al 2013). A recent review on safety of MRI has recommended a need for further studies as a precautionary principle (Hartwig et al, 2009).…”
Section: Genotoxic Effectsmentioning
confidence: 99%